Uniqueness of Modern Expression in Islamic Lyrics - Atajon Norov (Researchparks Publishing, 2022)
This article discusses the formal-stylistic, ideological-artistic features of modernist poetry. In particular, the unprecedented changes in artistic thinking that occurred at the end of the 20th century and the beginning of the new century made it possible to radically reform the level of philosophical coverage. As a result, poetry and poetry were closely observed as a huge issue and responsibility.